2020
DOI: 10.1161/circulationaha.119.044720
|View full text |Cite
|
Sign up to set email alerts
|

Low-Attenuation Noncalcified Plaque on Coronary Computed Tomography Angiography Predicts Myocardial Infarction

Abstract: Background: The future risk of myocardial infarction is commonly assessed using cardiovascular risk scores, coronary artery calcium score, or coronary artery stenosis severity. We assessed whether noncalcified low-attenuation plaque burden on coronary CT angiography (CCTA) might be a better predictor of the future risk of myocardial infarction. Methods: In a post hoc analysis of a multicenter randomized controlled trial of CCTA in patients with stable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
230
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 461 publications
(244 citation statements)
references
References 45 publications
6
230
0
8
Order By: Relevance
“…A prior study concluded that in symptomatic patients, LAP burden was the strongest predictor of myocardial infarction. 19 …”
Section: Discussionmentioning
confidence: 99%
“…A prior study concluded that in symptomatic patients, LAP burden was the strongest predictor of myocardial infarction. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Many papers have showed, that volumetric plaque analysis has additive information regarding CAD severity, disease progression and prognostication. [1][2][3][4][5] However, Symons et al indicated that there are significant variations in plaque volumes within 30 days even when the same scanner settings are used. Hence, significantly larger sample sizes are needed to achieve statistical significance due to the large test-retest variation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, it seems, that even among readers with considerable experience, there is substantial variation in contouring which leads to differences in plaque volumes. Unfortunately, this difference is largest in case of low-attenuation noncalcified plaque volume, which is currently of major research interest as it correlates with multiple clinical outcomes, [1][2][3][4][5] and therefore is seen as a potential pharmaceutical target. 6,7 Radiomic analysis is a promising new technique which may have the potential to increase the diagnostic accuracy of coronary CTA to identify vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Non-calcified plaque burden has been identified as an important predictor of future adverse cardiac events, particularly among symptomatic patients. 31 However, in asymptomatic patients, the use of coronary CT angiography to assess non-calcified plaque has not been shown to improve cardiovascular risk assessment when added to calcium scoring. 32,33…”
Section: Non-calcified Plaquementioning
confidence: 99%